Regarding the function of the Civil Court of Cassation in the field of civil rights protection - Stryzheus , Denys Anatoliyovych (Global Prosperity, 2022)
The article is devoted to theoretical and constitutional legal problems of judicial protection of civil rights. The author states that, taking into account the legal nature of justice, the judicial form of civil rights protection is the most perfect form of protection of the rights, freedoms and legitimate interests of subjects of civil legal relations. At the same time, attention is drawn to the fact that the judicial protection of civil rights is a democratic form of establishing the objective truth, since the courts are endowed with all the necessary powers to implement the human rights function. The above is confirmed, in the opinion of the author, by the fact that judicial protection of civil rights is enshrined at the level of the Constitution and branch laws of Ukraine, and is also singled out as a form of protection of civil rights of a person at the level of general principles of civil legislation, at the level of the modern model of specialized justice is a priority direction of the functioning of the state . Today, the system of judicial bodies providing judicial protection of civil rights in Ukraine is headed by the court of cassation instance - the Supreme Court (Article 388 of the Civil Procedure Code of Ukraine (hereinafter - the Civil Procedure Code of Ukraine), which includes the Civil Court of Cassation (Clause 5 of the second part of Article 37 of the Law of Ukraine "On the Judiciary and the Status of Judges"), which exercises independent procedural powers in the course of such protection of the civil rights of an individual. Since the court of cassation occupies the highest level in the system of judicial protection of civil rights, the author considers it expedient to analyze the peculiarities of the functional content of this court's activities. Functions The main directions and types of activities of the civil court of cassation as part of the Supreme Court, determined by its role and place in the judicial system (instance and specialization), which are carried out in procedural forms, within the limits and in the manner established by the Constitution and laws of Ukraine, are named in the article. It was found that the central element of such functions are the constitutional functions of the specified judicial body, which is determined by the legal supremacy of the Constitution of Ukraine and the normative material contained in it, in the system of legal regulation of the functions of the specified judicial authority. It is shown that the constitutional functions of the court of cassation in the field of protection of civil rights are, on the one hand, derived from the constitutional status of the relevant judicial body, and, on the other hand, reflect the general constitutional principles of the constitutional consolidation of elements of judicial protection of human rights.